2014
DOI: 10.1007/s11307-013-0713-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging Detects Impairment in the Retrograde Axonal Transport Mechanism After Radiation-Induced Spinal Cord Injury

Abstract: Purpose The goal of this study was to determine whether molecular imaging of retrograde axonal transport is a suitable technique to detect changes in the spinal cord in response to radiation injury. Procedures The lower thoracic spinal cords of adult female BALB/c mice were irradiated with single doses of 2, 10, or 80 Gy. An optical imaging method was used to observe the migration of the fluorescently labeled non-toxic C-fragment of tetanus toxin (TTc) from an injection site in the calf muscles to the spinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The LDI program consisted of 14 treatment fractions, each fraction administered once per day and delivering 2 Gy irradiation (a very small dose). Therefore, LDI could avoid the neurotoxicity of high doses of X-rays, which may contribute to necrosis, apoptosis, decrease in motor performance or death in rodents and humans (Ridet et al, 2000;Azria et al, 2012;Kim et al, 2013;LeRoux et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LDI program consisted of 14 treatment fractions, each fraction administered once per day and delivering 2 Gy irradiation (a very small dose). Therefore, LDI could avoid the neurotoxicity of high doses of X-rays, which may contribute to necrosis, apoptosis, decrease in motor performance or death in rodents and humans (Ridet et al, 2000;Azria et al, 2012;Kim et al, 2013;LeRoux et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Kalderon and Fuks (Kalderon & Fuks, 1996a,b) found that single-dose X-irradiation yielded beneficial effects on recovery in rats after hemisection of the corticospinal tract. However, single large doses of irradiation have shown a related neurotoxicity (Ridet et al, 2000;Azria et al, 2012;Kim et al, 2013;LeRoux et al, 2014). Low-dose fractionated irradiation (LDI) therapy is a powerful and safe procedure for removing the pathogenic cells.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their importance as virulence factors and biotherapeutics, BoNTs, TeNT and their recombinant fragments are also becoming increasingly popular as key tools of discovery to uncover deficits of axonal transport in animal models of neurological diseases (Bilsland et al, 2010;LeRoux et al, 2014;Malik et al, 2011;Schafer et al, 2017;Sleigh et al, 2017a;Sleigh et al, 2017b), ageing (Sleigh and Schiavo, 2016) and as flexible transsynaptic tracers (Coen et al, 1999;Kumar and Boehm, 2014).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…This may have a plethora of causes, for instance perturbed physical and chemical interactions with neighboring cells [ 10 ], altered activity [ 11 ], and insufficient maturation [ 12 ], which can only be convincingly overcome by studying transport in vivo. Several methods have been developed to study axonal transport en masse in live rodents [ 13 , 14 ]; however, these noninvasive techniques have limited temporal and spatial resolution and can be impacted by neuronal death. Although caveats apply, intravital imaging of axonal transport of individual cargoes is likely to provide more physiologically relevant insights into the process, while permitting detailed, real-time dissection of cargo dynamics [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inject the lateral head of the gastrocnemius using a steep angle from the plane of the table (Fig. 1c) and use a much shallower, almost horizontal, angle (i.e., [10][11][12][13][14][15][16][17][18][19][20] for the tibialis anterior ( Fig. 1d) (see Note 5).…”
mentioning
confidence: 99%